2021
DOI: 10.1029/2020jc017127
|View full text |Cite
|
Sign up to set email alerts
|

Global Chlorophyll a Concentrations of Phytoplankton Functional Types With Detailed Uncertainty Assessment Using Multisensor Ocean Color and Sea Surface Temperature Satellite Products

Abstract: As phytoplankton play a fundamental role in marine food webs and biogeochemical cycling, their community structure and taxonomic composition have been widely investigated in recent decades through various observational methods and ecological modeling (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…Our results also illustrate the potential for combining satellite data from multiple platforms in a neural network framework. The inclusion of ancillary environmental information such as water temperature and salinity can improve phytoplankton group modeling efforts (Figure S10 and Table S2 in Supporting Information S1; see also Brewin et al, 2019;Xi et al, 2021). Looking forward, the upcoming NASA Plankton, Aerosol, Cloud, and ocean Ecosystem (PACE) mission will include polarimetry and hyperspectral ocean color instruments that can potentially be combined with other remotely sensed or modeled data.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also illustrate the potential for combining satellite data from multiple platforms in a neural network framework. The inclusion of ancillary environmental information such as water temperature and salinity can improve phytoplankton group modeling efforts (Figure S10 and Table S2 in Supporting Information S1; see also Brewin et al, 2019;Xi et al, 2021). Looking forward, the upcoming NASA Plankton, Aerosol, Cloud, and ocean Ecosystem (PACE) mission will include polarimetry and hyperspectral ocean color instruments that can potentially be combined with other remotely sensed or modeled data.…”
Section: Discussionmentioning
confidence: 99%
“…Also, considering that the retrieval algorithm is an emerging technique, further research is necessary to investigate the over-estimation of the lower ranges and under-estimation of higher ranges of PFT Chla, and to promote the introduction of non-linear fitting in the regression model. Finally, another limitation of our EOFbased PFT analysis is the lack of estimation of per-pixel uncertainty, which to our knowledge has only been reported by Brewin et al (2017) and Xi et al (2021). In our study, we used OLCI R rs as the spectral input data derived through the POLYMER algorithm, and the uncertainty for the POLYMER derived R rs is currently under development (Steinmetz, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Bracher et al (2015) suggested that at least 50 valid matchup data points are necessary for statistically significant pigment estimation, specifically for open ocean waters. Xi et al (2020) employed a larger number of matchup data points for global open ocean waters, with an even higher number (483) in a more recent publication (Xi et al, 2021). Lange et al (2020) employed 73-78 matchup points to develop an EOF-based algorithm to retrieve phytoplankton cell abundance from MODIS across the Atlantic Ocean.…”
mentioning
confidence: 99%
“…In addition, a new high-resolution retrieval algorithm for column densities of BrO has been developed (Seo et al 2019). Long-term (2002-today) time series of phytoplankton groups were derived (Losa et al 2017;Xi et al 2021), which for the first time also deliver phytoplankton group data sets for the Arctic Ocean.…”
Section: B Satellite Data Analysismentioning
confidence: 99%